Fundamental study of oil palm fruit digestion process - Yayat Nurhidayat (2014)
Oil palm fruit digestion is an important step in palm oil milling process. After sterilization, the fruitlets are stripped and then fed to a digester where the fruitlets are heated with low pressure steam. Although the digestion is a simple process, the underlying fundamental principles governing the process are not well understood. To facilitate better understanding of its mechanism, the experimental work followed by the modelling and simulation of the digestion process were conducted on samples from different sterilized conditions, i.e. 40 and 70 psi. The study included the changes of physical, chemical, and mechanical properties of the samples, such as water and oil diffusivity, oil release rate, true and bulk density, compression test,dimension, mass, and volume, porosity, micro and meso structure of oil palm fruit fiber using SEM and microscope, oil released and water absorption during digestion process, oil extraction using hydraulic press, and also oil quality analysis. Bulk density of oil palm fruit decreased compared to sterilized fruit. Fracture resistance decreased consecutively, from fresh, sterilized, and digested fruit. In addition, fruit and shell of samples sterilized at 40 psi showed higher fracture resistance than that of 70 psi. However, compared to sterilized samples at 40 psi,samples sterilized at 70 psi demonstrated higher oil release and water absorption during digestion. Hydrolysis of cell walls is believed to promote higher oil liberation. This is indicated by higher sugar concentration in the digestion water condensate. During pressing, the optimum pressure of sterilized samples at 70 psi was lower than that of 40 psi demonstrated higher broken nut (kernel breakage) after oil extraction. The tests on oil quality namely deterioration of bleachabilty (DOBI), carotene content, free fatty acid (FFA) content, and triglycerides content were also investigated. Based on the analysis on samples of 40 and 70 psi sterilization conditions, no significant changes were found. Based on the standards established by MPOB, generally, the oil has good and acceptable quality. The computer simulation of microscale and mesoscale using Comsol Multiphysics version 4.4 was aimed to fully understand what really happen in the oil palm fruit digestion process. In the microscale, the study analyzed the fruit in cell levels, where oil globules, water content, cell walls of oil palm fruit exist which applied CFD and heat transfer module. The degree of cell wall rupture greatly affect oil movement. Fully ruptured cell wall promoted oil release. In the mesoscale level, the digestion process was applied to a single fruit of oil palm, consisting of mesocarp, shell, and kernel, while incorporating mass transfer of water and oil within mesocarp through the boundary and heat transfer. Sliced fruit had higher rate of oil released and water absorption. The results indicated that there is a good agreement between the simulated and experimental data at both scales of modelling.